Pengaruh Penerimaan Pajak Hotel, Pajak Restoran, Dan Pajak Hiburan Terhadap Pendapatan Asli Daerah Kota Malang Tahun 2016 - 2021 - Lis Lestari Sukartiningsih; Louise Erlanda Dwi Putri (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine the effect of hotel tax revenue, restaurant tax and entertainment tax on local revenue in Malang City in 2016-2021. This type of research is Explanatory Research, data collection methods use field studies and literature studies, with data analysis methods using quantitative descriptive statistical analysis. The data used in this study were obtained from the Malang City BKAD office, including the realization of hotel tax, restaurant tax, and entertainment tax revenue, as well as local revenue for 2016-2021. The results of multiple linear regression analysis show that hotel taxes, restaurant taxes, and entertainment taxes simultaneously affect local revenue. Partially, hotel taxes and entertainment taxes have no effect, the influential variable is restaurant taxes. The most dominant influencing variable is restaurant tax.